NEGATIVE IMPACTS OF FORCED MARRIAGE IN AISHA SAEED’S NOVEL WRITTEN IN THE STARS - Kahfiatika Kahfiatika; M. Manugeren (Universitas Islam Sumatera Utara, 2020)
Written in the Stars is a novel, written by Aisha Saeed. Written in the Stars was originally published in 2000 but republished again March 24th 2015. The story is about a Pakistani-American high school senior girl, torn between love for her culturally conservative immigrant parents and the boyfriend she keeps secret from them. When her outraged parents discover the romance, they take her and her brother on a vacation to visit relatives in rural Pakistan, with plans to force her into an arranged marriage to a local man. The objectives of this study are to find out the negative impacts of forced marriage in Aisha Saeed’s novel Written in the Stars and to describe the negative impacts of forced marriage. Qualitative Descriptive Research is appropriately applied in this study because this research shows the nature of the situation as it exists at the time of the study. The results of this study show that the implementation of Forced marriage only brings negative impacts to one or both parties. There are two forms of negative impacts found: violence and loss of social relationship. Violence is again divided into two forms: physical violence and verbal abuse.